STRATEGI KOMUNIKASI PERSUASIF KADER POSYANDU REMAJA (TEMAN SEHAT) DALAM MENINGKATKAN KESADARAN REMAJA PADA BAHAYA STUNTING DI DESA NAMBANGAN KECAMATAN SELOGIRI KABUPATEN WONOGIRI - Putri Ananto, Nabila; Itasari, Andri Astuti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The youth posyandu program carried out by youth posyandu cadres (Teman Sehat) is one of the initiatives by the Wonogiri district government aimed at reducing the stunting rate in Wonogiri to zero stunting. This program targets the health of adolescents aged 10 to 18 years. The objective of the program is to explore the persuasive communication strategies employed by youth posyandu cadres (Teman Sehat) to raise awareness among adolescents about the dangers of stunting in Nambangan village. The youth posyandu cadres use persuasive communication to convey messages and encourage adolescents to follow their guidance. This study analyzes the communication process using McGuire's persuasive communication theory. Severin and James state that “information processing theory” is employed in this research, which utilizes a qualitative research method with a descriptive approach. The data in this study consists of primary data from interviews, observations, and documentation, as well as secondary data from relevant literature reviews. Informants in this research were selected using purposive sampling techniques. The research findings indicate that the persuasive communication strategies implemented by youth posyandu cadres can change the mindset and lifestyle of adolescents aged 10 to 18 years after participating in a series of youth posyandu activities. Adolescents become increasingly aware of the importance of stunting prevention for themselves. Keywords: Youth posyandu cadres, persuasive communication strategies, adolescent awareness, stunting.The youth posyandu program carried out by youth posyandu cadres (Teman Sehat) is one of the initiatives by the Wonogiri district government aimed at reducing the stunting rate in Wonogiri to zero stunting. This program targets the health of adolescents aged 10 to 18 years. The objective of the program is to explore the persuasive communication strategies employed by youth posyandu cadres (Teman Sehat) to raise awareness among adolescents about the dangers of stunting in Nambangan village. The youth posyandu cadres use persuasive communication to convey messages and encourage adolescents to follow their guidance. This study analyzes the communication process using McGuire's persuasive communication theory. Severin and James state that “information processing theory” is employed in this research, which utilizes a qualitative research method with a descriptive approach. The data in this study consists of primary data from interviews, observations, and documentation, as well as secondary data from relevant literature reviews. Informants in this research were selected using purposive sampling techniques. The research findings indicate that the persuasive communication strategies implemented by youth posyandu cadres can change the mindset and lifestyle of adolescents aged 10 to 18 years after participating in a series of youth posyandu activities. Adolescents become increasingly aware of the importance of stunting prevention for themselves.Keywords: Youth posyandu cadres, persuasive communication strategies, adolescent awareness, stunting.